Outsourcing transitions and the employment relationship implications. (26th April 2017) - Mitchell, Ivan; James, Phil
Abstract: Drawing on three longitudinal case studies involving the outsourcing of public leisure services, we explore the work transitions of staff as they transfer from one organisation to another using a three‐phase analytical framework. The findings confirm the idea that outsourcing can be a difficult transition to go through, with losses occurring in relation to terms and conditions of employment. However, they also show how such changes can occur alongside the development of seemingly positive employment relationships with the new employer that challenge the view that the employment effects of public service outsourcing are invariably perceived in a negative light by employees. In doing so, the study's findings are seen to point towards the value of exploring outsourcing‐related work transitions longitudinally and through the lens of the adopted analytical framework. They are also seen to have implications for how such transitions are theorised and managed, including how we might understand the nature of the employment relationship and the role of line managers.